Methods used by the United States National Institute for Occupational Safety and Health to monitor crystalline silica - Lorberau, C. D.; Abell, M. T. (Scandinavian Journal of Work, Environment & Health, 1995)
The National Institute for Occupational Safety and Health (NIOSH) in the United States has four methods for monitoring the concentration of crystalline silica dust. They all employ a cyclone for size-selective sampling in the field, but differ primarily in that the laboratory measurement is based on either infrared spectroscopy, X-ray diffraction, or colorimetry. The limits of detection for these methods are similar, but their accuracy is poor, particularly at low filter loadings near the current recommended exposure limit (50 µg·m-3). Advances in analytical instrumentation have improved measurement precision. Correction techniques to account for X-ray absorption in samples loaded with nonsilica dust have eliminated one source of bias. Direct analysis on collection filters is a convenient technique that should decrease sample manipulation errors, but it has not been shown to improve precision or accuracy significantly.
Keywords: dust analysis; exposure limit; infrared spectroscopy; size selective sampling; X-ray diffraction